GRAMMAR MASTERY FOR HOSPITALITY AND TOURISM STUDENTS: TO WHAT EXTENT DOES IT MATTER FOR THEIR FUTURE CAREER? - Widianingtyas, Nugraheni; Silalahi, Ronald Maraden Parlindungan; Aolia, Fahri (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
There have been pros and cons to learning grammar concerning Second Language Acquisition. This paper aims to investigate Hospitality and Tourism (HT) students’ and workers’ perceptions of the significance of English grammar which has not been widely discussed. This article reports a mixed-method study that was conducted using an online survey and involving 50 HT students and 50 HT workers across Indonesia. Interviews with 2 Human Resource Managers of international hotel chains were also performed to provide stronger validation. The findings revealed that HT students and workers do not hold a positive perception of learning grammar and should not comprehensively learn English rules since grammar mastery will insignificantly impact employability and career performance for most positions in that sector. However, it is suggested that those in higher positions learn the 6 most commonly used tenses to avoid misunderstandings that, to some degree, link to job promotions. Results also suggest that teachers of ESP for Hospitality prioritize students’ speaking fluency, listening, and vocabulary comprehension using the CLT and PBL teaching approaches. The research results are expected to build a more positive attitude toward English learning, thus fostering a better quality of human resources in the hospitality industry.